Realizing the Promise of Social Assistance : Cambodia Policy Note - Zambra, Claudia (World Bank, Washington, DC, 2018)
Although Cambodia has become one of the world’s leaders in poverty reduction, two-thirds of its population remains poor or economically vulnerable, with a large number of households moving in and out of poverty. Cambodian households are exposed to a range of shocks that can have devastating costs for the poor and vulnerable. Negative coping strategies to manage shocks can put poor or economically insecure households at risk of a return to or deepened poverty. Formal social protection in Cambodia is only incipient, with low levels of spending compared to other countries, particularly for social assistance. Most social protection spending in Cambodia goes toward retirement benefits for civil servants through the National Social Security Fund for Civil Servants (NSSF-C) and the National Fund for Veterans (NFV), neither of which have been contributory to date and are thus entirely funded through general revenues. Social assistance spending is much lower and comprises several small, fragmented programs. The Government has recently signaled its willingness to scale up social assistance through its approval of the National Social Protection Policy Framework (NSPPF), which lays out ambitious reforms. The NSPPF, approved in 2017, provides the framework for an integrated social protection system. Guidance will be provided by a National Social Protection Council (NSPC) under the overall direction of the Ministry of Economy and Finance (MEF), with distinct sub-bodies for social insurance and social assistance. This note presents policy options for ensuring the feasibility of the institutional and programmatic rollout of social assistance reforms envisaged in the NSPPF. To realize the goals of the NSPPF, a clear vision on prioritization and sequencing of SA reforms will be critical. The path from incipient and fragmented social assistance systems is one that has been trodden by many developing countries in recent years, and those experiences can provide important lessons for Cambodia in this process. This policy note draws from these lessons while taking into account Cambodia’s ongoing social assistance programs, institutional frameworks, and delivery systems. It utilizes the World Bank’s ASPIRE database, program documents, an assessment of Cambodia’s social assistance programs in the OECD’s 2017 Social Protection System Review of Cambodia, and country data.